PERANCANGAN SISTEM PLAMBING AIR LIMBAH GEDUNG RASUNA SAID OFFICE TOWER, JAKARTA - Ega Prawira, Harpa
Tower building is a building type that is commonly used for human activities in many ways one of which as an office function. Tower building is an efficient building for a minimal availability of land in urban areas that are considered suitable for a variety of functions including the office function, such as Rasuna Said rental office Building, Jakarta. Every human activity or business basically impact on the environment so that is necessary to control negative impacts as early as possible. One of the waste that generated by the office activity in the building is domestic wastewater. And there are also rain water runoff that must be controlled. So, it is necessary to design sewage and drainage system as an control to the impact. The design method is divided into the study of literature as an initial procedure, collecting supporting data, and the last one is planning phase. Based on the results of the design, the range size of pipe diameter is about 50- 250mm for blackwater and for greywater 32-150 mm..And slope for piping between 1/50 - 1/100. For vent piping system, the size range is about 32-150 mm. Basically the sewage system is divided into greywater and blackwater in accordance with the designation initially, in addition, the entire sewage system implementing gravity force.Therefore, drainage system utilize piping and guttermethod. And rain water also used as a source of fresh water for rain water harvesting in this building.